Liquid formulation of CRIJAF SONA: A new beginning in jute retting - Majumdar, Bijan; Mazumdar, Sonali Paul; Sarkar, Sitangshu; Kar, Gouranga (Indian Farming, 2022)
CRIJAF SONA, a talc-based microbial formulation has already been popularized among farming communities for faster retting and fibre quality improvement of jute. The endospores based liquid formulation of CRIJAF SONA is developed to increase its shelf life to overcome the comparatively shorter shelf life of its talc based formulation. The liquid formulation of CRIJAF SONA proved to be more resistant to environmental stress, with higher shelf life and very efficient in faster retting of jute resulting in fibre quality improvement. This would be very beneficial for the jute farming community since they would not need to worry about the availability of huge quantity of water for retting and would be quite sure about the quality of retted jute fibre. Hence, would help increase farmer’s income.